Comparison of hemocyte parameters in the pericardial cavity and the adductor muscle sinus in the Pacific oyster, Crassostrea gigas using two types of flow cytometers - Gagnaire, Béatrice; Duchemin, Matthieu; Auffret, Michel; Thomas-Guyon, Hélène; Renault, Tristan (HAL CCSD, 2008)
International audience Parameters of hemocyte populations have been considered as relevant indicators of bivalve health and are currently used in immunotoxicological studies. Hemocytes in hemolymph can be collected by puncturing either the pericardial cavity or the adductor muscle sinus with a syringe. Flow cytometry is a methodological approach that is increasingly being used in laboratories for the study of hemocyte parameters in aquatic invertebrates. However, various protocols for hemocyte processing in laboratories equipped with different types of cytometers have been published. In this context, two flow cytometers (EPICS XL4®, Beckman Coulter and FacsCalibur®, Becton Dickinson) and two sites of hemocyte collection (pericardial cavity and adductor muscle sinus) were compared for the analysis of hemocyte parameters in the Pacific oyster, Crassostrea gigas. Hemolymph cells were analyzed in terms of their number and organelle contents. Cell mortality, phagocytosis, non specific esterase, extension of the lysosomal compartment and production of reactive oxygen species were quantified. The results showed that the phagocytic index was higher for hemocytes obtained in the muscle sinus hemolymph. The results ar